1997
DOI: 10.1093/cercor/7.4.303
|View full text |Cite
|
Sign up to set email alerts
|

The development of auditory callosal connections in normal and hypothyroid rats

Abstract: Previous studies have shown that hypothyroidism modifies the development of callosal connections. In particular, adult hypothyroid rats have fewer callosally projecting neurons in layers II-III of the auditory cortex and more in layer V. This might be due to disturbance in the stabilization/elimination of juvenile callosal axons, or to abnormal neuronal migration during cortical histogenesis. To distinguish between these possibilities we have studied the distribution of callosally projecting auditory neurons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 52 publications
0
47
0
Order By: Relevance
“…The observed reduction in the thickness of the stratum radiatum in LID-1 and LID-2 pups suggests a reduction in the length of apical dendrites of pyramidal neurons, such as has been reported in granule and pyramidal cells of the hippocampus of goitrogen-treated hypothyroid rat pups (49). It is very likely that abnormal migration also results in aberrant circuits in the neocortex and the hippocampus in the progeny of LID-1 and LID-2 dams, considering that changes in GABAergic (50) and in callosal (27,51) and thalamocortical connections (29) have been found in goitrogen-treated rat pups, in which altered migration also occurs and barrel formation is deranged. Identification of detectable functional deficits caused in the rat by the anatomical alterations described here will require further studies.…”
Section: Figurementioning
confidence: 83%
See 2 more Smart Citations
“…The observed reduction in the thickness of the stratum radiatum in LID-1 and LID-2 pups suggests a reduction in the length of apical dendrites of pyramidal neurons, such as has been reported in granule and pyramidal cells of the hippocampus of goitrogen-treated hypothyroid rat pups (49). It is very likely that abnormal migration also results in aberrant circuits in the neocortex and the hippocampus in the progeny of LID-1 and LID-2 dams, considering that changes in GABAergic (50) and in callosal (27,51) and thalamocortical connections (29) have been found in goitrogen-treated rat pups, in which altered migration also occurs and barrel formation is deranged. Identification of detectable functional deficits caused in the rat by the anatomical alterations described here will require further studies.…”
Section: Figurementioning
confidence: 83%
“…One series was processed for BrdU immunocytochemistry, and an adjacent series was stained with cresyl violet (SigmaAldrich, St. Louis, Missouri, USA). For BrdU immunocytochemistry, we followed the procedure of Lucio et al (27), using BrdU mouse Ab (Amersham Pharmacia Biotech Ltd., Little Chalfont, Buckinghamshire, UK), biotinylated horse anti-mouse Ab, an ABC kit (both from Vector, Burlingame, California, USA), and 3,3′-diaminobenzidine (DAB, Sigma-Aldrich). A second series was incubated only with anti-mature neurons neuronal nuclei (NeuN) mouse Ab (1:100, Chemicon International Inc., Temecula, California, USA), biotinylated horse antimouse Ab, ABC, and DAB.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…in Zoeller and Rovet, 2004;Bernal, 2005;Bernal, 2007;Williams, 2008). The events controlled by THs comprise cellular proliferation, migration, and neuronal and glial cell differentiation (Narayanan and Narayanan, 1985;Berbel et al, 1993;Berbel et al, 1994;Lucio et al, 1997;Auso et al, 2004;Cuevas et al, 2005). Clinical and experimental studies have demonstrated that THs are essential for normal brain development.…”
Section: Nervous Systemmentioning
confidence: 99%
“…These deficits depend on specific cellular impairments. Indeed, during the prenatal period, THs influence neurogenesis, neuronal proliferation and migration in the cerebral cortex, hippocampus and medial ganglionic eminence (Narayanan and Narayanan, 1985;Lucio et al, 1997;Auso et al, 2004;Cuevas et al, 2005). Axonal outgrowth, dendritic branching and synaptogenesis, together with the initiation of glial cell differentiation and migration are also affected by TH deficiency at prenatal stages (Portfield and Hendrich, 1993;Morreale de Escobar et al, 2000;Bernal et al, 2003).…”
Section: Nervous Systemmentioning
confidence: 99%